The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2nr02027k
|View full text |Cite
|
Sign up to set email alerts
|

Ball milled glyco-graphene oxide conjugates markedly disrupted Pseudomonas aeruginosa biofilms

Abstract: The engineering of the surface of nanomaterials with bioactive molecules allows controlling their biological identity thus accessing to functional materials with tuned physicochemical and biological profiles suited for specific applications....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…However, previous reports have shown that the size of nanomaterials prepared through ball-milling was relatively large. [174][175][176] Very few reports have produced quantum-sized materials from layered materials through ball-milling. Yang et al prepared CQDs from activated carbon by high-energy ball-milling (HEBM).…”
Section: Mechanical Exfoliationmentioning
confidence: 99%
“…However, previous reports have shown that the size of nanomaterials prepared through ball-milling was relatively large. [174][175][176] Very few reports have produced quantum-sized materials from layered materials through ball-milling. Yang et al prepared CQDs from activated carbon by high-energy ball-milling (HEBM).…”
Section: Mechanical Exfoliationmentioning
confidence: 99%
“…In contrast to graphene, GO is relatively easy to functionalize, owing to the varied functionalities, mainly epoxide and hydroxyl groups, on its surface. [11][12][13] Importantly, GO is rapidly degraded by human peroxidases avoiding longterm side effects that might be associated with bioaccumulation. [14] In the field of drug delivery, size and functionalization play an important role on how cells and tissues interact with materials.…”
Section: Introductionmentioning
confidence: 99%
“…Such a characteristic is key in terms of forming stable GO colloids in water and/or in polar solvents. In contrast to graphene, GO is relatively easy to functionalize, owing to the varied functionalities, mainly epoxide and hydroxyl groups, on its surface [11–13] . Importantly, GO is rapidly degraded by human peroxidases avoiding long‐term side effects that might be associated with bioaccumulation [14] …”
Section: Introductionmentioning
confidence: 99%
“…Among carbon nanomaterials, graphene oxide (GO) shows extensive multifactorial properties: stretchability, electrical and high thermal conductivity, and a large surface area that allows functionalisation with antimicrobial compounds. Moreover, GO has antimicrobial properties that can vary depending on the GO sheets’ dimension and the environment [ 20 , 21 ]. Briefly, GO displays three different antimicrobial mechanisms: GO sharp edges can physically cut the membrane, with the consequent leakage of the intracellular contents, GO can also induce the production of ROS, and, finally, GO sheets can wrap around microorganisms, isolating them from the environment, limiting the adsorption of nutrients, and stopping the proliferation [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%